Friction Characterisation for a Tumbling Self-Piercing Riveting Process - Wituschek, Simon; Lechner, Michael (Key Engineering Materials, 2021)
Due to increasing demands regarding ecological and economic specifications in vehicle design, the effort required for production is continuously increasing. One trend is the increased use of multi-material systems, which are characterised by the use of different materials such as high-strength steels or aluminium alloys. In addition to the varying mechanical properties of the components, an increased number of variants accompanied by different geometries is leading to increasing challenges on body construction. For the assembly and connection of the individual components, conventional joining methods reach their limitations. Therefore, new joining methods are necessary, which feature properties of versatility and can adapt to process and disturbance variables. One way of achieving tailored joints is to use a tumbling self-piercing riveting process. For the design of the process route, numerical investigations are necessary for which a characterisation of the friction properties is necessary. This paper therefore investigates the contact and friction conditions that occur in a tumbling self-piercing riveting process. The individual contacts between the process components are identified and based on this, suitable processes for the characterisation of the friction factors - and coefficients are selected and performed.
Keywords: Friction; Joining; Self-Piercing riveting